The impact of patient-reported visual disturbance on dynamic visual acuity in myopic patients after corneal refractive surgery - Wang, Yuexin; Zhang, Yu; Wu, Tingyi; Ren, Xiaotong; Yuan, Yifei; Li, Xuemin; Chen, Yueguo (Frontiers in Neuroscience, 2023)
Purpose To investigate the impact of patient-reported visual disturbance on dynamic visual acuity in myopic patients after corneal refractive surgery. Methods This is a prospective nonrandomized study. Adult myopic patients receiving bilateral photorefractive keratectomy (PRK), femtosecond laser-assisted in situ keratomileusis (FS-LASIK), or small incision lenticule extraction (SMILE) with Plano target were included. Eight types of patient-reported visual disturbance were evaluated regarding frequency, severity and bothersome and dynamic visual acuity (DVA) of 40 and 80 degrees per second (dps) was measured postoperatively at 3 months. Results The study enrolled 95 patients with an average age of 27.6 ± 6.4 years. The most frequently reported visual disturbance was the fluctuation in vision (70.5%), followed by glare (66.3%) and halo (57.4%). Postoperative DVA at 80 dps was significantly associated with the total score of haloes (p = 0.038) and difficulty in judging distance (p = 0.046). Significant worse postoperative DVA at 40 dps was observed in patients with haloes than those without (p = 0.024). The DVA at 80 dps for patients without haloes or difficulty in judging distance was significantly better than that with the symptoms (haloes, p = 0.047; difficulty in judging distance, p = 0.029). Subgroup analysis by surgical procedures demonstrated that the significant difference in DVA between patients with and without visual disturbance was only observed in patients receiving FS-LASIK. Conclusion Postoperatively, myopic patients undergoing corneal refractive surgery with haloes or difficulty in judging distance have significantly worse low and high-speed DVA than those without the symptoms. The present study provided the basis for postoperative guidance in daily tasks involving dynamic vision when patients have visual disturbances.